O impacto da consultoria ontopsicológica no desempenho organizacional - Bazzo, Paula Silva (2011)
The objective of this research was to investigate the application of the ontopsychological business consulting model in Brazilian organizations and the perception of the results obtained by it diagnosis. The work structure presents first the historical and conceptual aspects of business consulting, and then reported a few models of it, devoting more attention to the ontopsychological model. With a qualitative and exploratory approach, this study concentrates it analysis on the cases of three companies with 100% Brazilian capital, through semi-structured interviews. The series of interviews was built through three main axes: initial approach, process and results. The sample was selected by convenience, totaled 14 subjects: five consultants, who use this model in their jobs, and nine entrepreneurs of the three companies surveyed. The collected data were classified by content analysis into five categories that emerged from both theoretical discussions and interviews. Among the results shown in the companies studied, we highlight the economic, the individual, the management and the business dynamics gains arising from the application of this model. Moreover, it was found that it is a model which attention is directed to the personality of the main leadership and how it materializes in the organization, enhancing interdisciplinary discussion in the administrative area.